KUALITAS PELAYANAN PERALIHAN HAK JUAL BELI ATAS TANAH PADA KANTOR PERTANAHAN KOTA PALU PROVINSI SULAWESI TENGAH - Utami, Maria Emi Wulan; Pasinringi, Andi; Susanti, Ani (Katalogis, 2019)
The implementation of land registration at the Palu City Land Office for the community will receive legal certainty regarding the transfer of land rights due to the sale and purchase. In addition, there will be a letter of proof of legal and strong rights called a certificate of land rights. Certificates are issued so that holders of land rights can easily prove their new juridical data rights / name of new rights owner. The purpose of this study was to find out the quality of service for the transfer of sale and purchase rights to land at the Land Office of Palu City, Central Sulawesi Province. This research uses descriptive qualitative type, with the number of informants involved as many as 7 informants through Purposive Sampling techniques. In addition, in the data collection technique in this study through observation, interviews and documentation. With the method of data analysis through the stage of condensation data, display data, and draw conclusions or verification. Data condensation refers to selecting, focusing, simplifying, abstracting, and transforming. From the results of the research, it is known that the quality of service for the transfer of rights to buy land on the Palu City Land Office in Central Sulawesi Province is still considered to be less than optimal, this can be seen after going through the data analysis process showing that there are two aspects that are not good, both aspects are responsiviness and assurance.